High Rice Import as a Threat to Food Security and a Hindrance to Sustainable Rice Production in Ghana - , Ayisi Daniel Nyarko, Zsuzsanna Kassai (Archives of Current Research International, 2017)
Aims: The main objective of this study is to analyse the extent to which Ghana depends on rice import to satisfy domestic food needs and how it affects domestic rice production. Study Design: The study employed a case study technique. Methodology: Both quantitative and qualitative methods were used. Secondary data from the databases of the Food and Agriculture Organization of the United Nations, the Ministry of Food and Agriculture, the United States Department of Agriculture, Index Mundi and other sources were used. The data of domestic rice production, imports and consumption were studied over a ten-year period. The average annual consumption per capita values were obtained by dividing the total annual rice consumption for each year by the total population for that particular year. Results: It was observed that rice imports in Ghana outweigh its domestic production level; it has an imports dependency gap of 61.08% which was 568 thousand metric tonnes in 2014. Also Government expenditure on rice imports stood at 500 million US dollars in 2014, which represented a 259.87% increase since 2005. Conclusion: It was concluded that Ghana is food insecure in terms of rice consumption; since it depends largely on imported rice to meet its domestic demand. Therefore, any decisions by the leading rice exporting countries to ban or reduce the quantity of rice supply to Ghana may cause food shortage and hunger. It was therefore recommended that the government should allocate a quota to rice imports instead of increasing import tariff, and more resources should also be allocated to rice production to expand the current production levels.